1991
DOI: 10.3109/14756369109069057
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Models for the Chemical Nature of Endogenous Digitalis

Abstract: The inability or the capacity to promote the phosphorylation of Na+/K(+)-transporting ATPase (Na/K-ATPase) from [32P]Pi is shown to differentiate between mechanistically digitalis-unlike and digitalis-like inhibitors of this enzyme known to be the receptor for all digitalis actions. A negative or positive response in the phosphorylation promotion assay introduced here appears thus to be suitable to diagnose the chemical species in the isolates of animal origin related to the putative endogenous digitalis. Vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Although the chemically modified bufadienolide derivatives formally belong to the steroid group, they are lacking the basic structural requirements for glucocorticoid activity, namely the ketone group at C3, the D4,5 double bond, the ketol side chain at C17, and especially the hydroxyl group at C11 [38]. Moreover, in contrast to hormonal steroids, they all have a C/D cis-junction typical for cardiac steroids [39]. Therefore, the chemical changes which abrogated cardiac activity did not transform the substances into glucocorticoid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Although the chemically modified bufadienolide derivatives formally belong to the steroid group, they are lacking the basic structural requirements for glucocorticoid activity, namely the ketone group at C3, the D4,5 double bond, the ketol side chain at C17, and especially the hydroxyl group at C11 [38]. Moreover, in contrast to hormonal steroids, they all have a C/D cis-junction typical for cardiac steroids [39]. Therefore, the chemical changes which abrogated cardiac activity did not transform the substances into glucocorticoid hormones.…”
Section: Discussionmentioning
confidence: 99%
“…Related to the stereochemistry of C/D rings junction, megestrol acetate and chlormadinol acetate (CMA), bearing C/D trans junction, inhibit Na + ,K + -ATPase [88]. CMA showed a potency similar to digitoxigenin in in vitro 3 H-ouabain binding assays.…”
Section: Pregnane Derivativesmentioning
confidence: 99%
“…Another argument is that cardiac glycosides do not produce hypertension at therapeutic doses. Some authors even speculate with certain C/D trans steroidal hormones as models for the chemical structure of endogenous digitalis [88]. They have also been proposed synthetic candidates as EDLF analogues [102].…”
Section: Endogenous Digitalis-like Factorsmentioning
confidence: 99%
“…1e,6 Its main chemical features are (a) a lipophilic perhydrophenanthrene nucleus; (b) the presence of an R,β-unsaturated ester moiety, a feature common to the 17β-substituents of classic cardioactive steroids; (c) a basic residue which is essential for its activity. 6 The importance of an ionic interaction in the region of the 17-substituent of Na + ,K + -ATPase inhibitors has been demonstrated by SAR studies also for digitalis-like compounds. 1a,5,7,8 In 1991, R. W. Baker et al 9 reported the synthesis of a series of cassaine analogues and demonstrated a significant contribution to the binding energy displayed by a hydrophobic interaction in the R region, approximately corresponding to the D-ring of digitalis compounds (C15-C16).…”
Section: Introductionmentioning
confidence: 99%